Importance of accounting for sibling age when examining the association between family size and early childhood cognition, language and emotional behaviour: a birth cohort study. Issue 3 (19th March 2021) - Symeonides, Christos; Vuillermin, Peter J; Sciberras, Emma; Senn, Elizabeth; Thomson, Sarah M; Wardrop, Nicole; Anderson, Vicki; Pezic, Angela; Sly, Peter D; Ponsonby, Anne-Louise
Abstract : Objectives: Larger sibships are associated with poorer cognitive and language outcomes but have different impacts on child emotional development. Previous studies have not taken into account sibling age, nor have impacts across multiple neurodevelopmental domains been considered in the same participant group. This study investigated the influence of family size indicators on early childhood cognitive, language and emotional-behavioural development. The effect of sibling age was considered by evaluating these relationships separately for different sibling age categories. Design: Prospective birth cohort study. Setting: Participants in the Barwon Infant Study were recruited from two major hospitals in the Barwon region of Victoria, Australia, between 2010 and 2013 (n=1074 children). Participants: The 755 children with any neurodevelopmental data at age 2–3 years excluding twins and those with an acquired neurodisability. Outcome measures: Cognitive and language development was assessed using the Bayley Scales of Infant and Toddler Development, Third Edition, and emotional-behavioural development was measured with the Child Behaviour Checklist for Ages 1½−5. Results: Greater household size was associated with a reduced cognitive development score (adjusted mean difference (AMD) −0.66 per extra household member; 95% CI −0.96 to –0.37; p<0.001) without age-specific differences. However, poorer expressive language was only observed for exposure to siblings between 2–6 and 6–10 years older. Having siblings 2–6 years older was associated with less internalising behaviour (AMD −2.1 per sibling; 95% CI −3.1 to –1.0; p<0.001). These associations persisted after multiple comparison adjustment. Conclusions: The influence of siblings on early childhood development varies substantially by sibling age and the neurodevelopmental outcome under study. Although family size alone appears important for cognitive development, age-specific findings emphasise the importance of sibling interaction in early childhood expressive language development and emotional behaviour.